HEALTH EFFECTS OF HOT SUMMER WEATHER IN PATIENTS WITH INTERMEDIATE AND HIGH CARDIOVASCULAR RISK - M. D. Smirnova (Кардиоваскулярная терапия и профилактика, 2013)
Background. The potential global warming justifies the need for further investigation of the impact of abnormally hot summer weather on health and the prevention of these negative health effects.Aim. To study the effects of extreme climatic conditions (hot weather) on hemodynamics, electrolyte metabolism, oxidative stress (OS), and quality of life (QoL) in cardiac patients.Material and methods. In total, the study included 123 patients (52 men and 76 women) with intermediate (17,3%) and high or very high (82,7%) cardiovascular risk. The following parameters were assessed: office blood pressure (BP), pulse wave velocity (PWV), plasma levels of potassium (K), sodium (Na), oxidized low-density lipoproteins (oxLDL), and malondialdehyde (MDA), erythrocyte activity of superoxide dismutase (SOD), and MDA/SOD ratio. The QoL scale, Shikhan clinical anxiety scale, and a questionnaire specifically designed for this study were also used.Results. Subjective health deterioration in hot weather was reported by 46,3% of the participants. The number of cardiovascular events (CVE) was higher during the hot weather period, compared to the following period (p=0,009). Hot weather was associated with a reduction in the levels of systolic BP (SAD; p=0,004), diastolic BP (DBP; p=0,04), PWV (p=0,05), and heart rate (HR; p=0,06). The levels of Na were elevated by the second visit (p=0,002). The number of CVE during the hot weather period negatively correlated with the dynamics of PWV (r= –0,304, p<0,001), SBP (r= –0,225, p=0,009), and DBP (r= –0,292, p=0,001) and positively correlated with the Na concentration dynamics. There was a negative correlation between QoL and age (r= –0,202, p=0,03). The hot weather period was characterised by the OS development, with the OS regression during the subsequent colder period.Conclusion. Hot summer weather, even within the climatic norm range, is associated with increased CVE risk in some cardiac patients. Negative health effects of hot weather were self-reported by 46,3% of participants. Inadequate heat adaptation was linked to OS development, lesser degree of BP and PWV reduction, more pronounced Na elevation, and older age.